"It Bothers Me, but I Will Not Bring It into the Kindergarten": Gender Perception Conflicts of Religious Kindergarten Teachers as Reflected in Their Work. Issue 4 (8th August 2019) - Achituv, Sigal
Abstract: The article describes a study on the gender identity of kindergarten teachers in the Israeli State Religious Education System (Hemed). The aim was to investigate their perception of gender identity in light of Orthodox feminism and discover how this is reflected in their work, particularly in the Torah stories they tell. The study, based on a narrative research method comprising seven teachers, suggested a link between their gender perceptions and attitude toward Orthodox feminism, and their attitude toward patriarchal Bible stories. The discomfiture and internal contradictions characterizing their perceptions reflect the diverse attitudes in the religious public to this issue.